Társadalmi különbségek a gyermekek egészségi állapotában Magyarországon a 21. század második évtizedében - Tamás Hajdu; Gábor Kertesi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
– Our study examines social differences in health during childhood and adolescence in Hungary in the 2010s. For this analysis, we have collected administrative and survey data sources and organized them into a coherent statistical framework. These restructured data have been used to identify social inequalities in children's health and the possible causes of these inequalities. Our research shows that children's health is strongly related to the social environment in which they are born, their living conditions and income, and the behavioral characteristics of themselves and their parents.
Keywords: I12; I14; J13; 330; health; health behavior; housing conditions; inequality; children; Hungary